AMERICA AND POLITICAL OPPOSITION IN CENTRAL ASIA - ERGASHEV, Bakhodyr (CENTRAL ASIA AND THE CAUCASUS, 2005)
Political opposition in all Central Asian countries is still weak: the dissident parties and groups are not strong enough to cope with the state, their opponent, which is omnipotent.1 Late in the 1990s the United States realized that rather than addressing specifically European or Asian tasks, in Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan it has to create a certain Eurasian model of its attitude toward their political systems. The threat of international terrorism and Islamic extremism is too real to allow Washington to treat the democratic groups in Central Asia in the same balanced way similar groups in Central and Eastern Europe are treated. Still, the White House is fully aware of the importance of the current situation in Central Asia for continued stability and order the world over